The raven and the falcon : youth versus old age in medieval Arabic literature - Shuraydi, Hasan. (Islamic History and Civilization, 2014)
This book fills a long-standing gap in Arabic-Islamic studies. Following the informative and entertaining style of adab literature and based on a large number of relevant sources from a wide range of genres, Hasan Shuraydi presents a panoramic view of relevant themes that concern youth and old age in Medieval Arabic literature intended for both specialists and non-specialists. A pattern of binary oppositions runs through such themes, e.g., black/white, male/female, husband/wife, sacred/profane, paradise/this world, ignorance/wisdom, past/present, young/old, new/old, health/disease, sappy/dry, permitted/forbidden, lust/chastity, obedience/disobedience, experience/inexperience, folly/reason, sobriety/intoxication, parent/child, celibacy/marriage, present life/hereafter. Themes discussed include: aging, ambition, aphrodisiacs, beauty, education, feminist trends, hair dyeing, homosexuality, honoring age, jihad, life stages, longevity, love, marriage, sex.